Selected area hot machining with a multi-tipped diamond tooling system. - Dennis, Ashley (Cranfield University, 2017)
An investigation of a novel ultra-precision tool is presented, the hot-milling multi-turret diamond tool. The tool implements micro-Laser Assisted Machining (μ-LAM) upon a multiple diamond fly cutter. Details of its design, both mechanical and optical, are presented- along with proposed modifications to Cranfield University’s Tetraform C machine to allow for its implementation. Relevant experimentation is presented- the modal analysis of the Tetraform C machine and the testing of laser heating on a silicon substrate. FE analyses are carried out and calculations presented to justify design choices. Analytical investigations predicted increased depths of cut by using laser, and indicated that at lower wavelengths of laser light and with lower feed rates that the depth of cut may be significantly increased. A novel method of selecting laser wavelength based upon change in material absorptivity with temperature is investigated which may offer substantial increases in μ-LAM performance
Keywords: hot milling; multi-tip; fly-cutter; UPRM; UPFC; μ-LAM